2016
DOI: 10.2147/cia.s104599
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between vitamin D levels and apoptosis in geriatric patients infected with hepatitis C virus genotype 4

Abstract: BackgroundVitamin D levels play a pivotal role in most biological processes and differ according to age. A deficiency of vitamin D in chronic hepatitis C (CHC) patients has been shown to be linked with the severity of liver fibrosis, but little is known about the mechanism of this association.ObjectiveIn this study, we evaluate the potential interrelation between vitamin D levels, oxidative stress, and apoptosis, based on liver fibrosis in geriatric patients infected with hepatitis C virus (HCV) genotype 4.Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 104 publications
(109 reference statements)
0
7
0
Order By: Relevance
“…106,135 Apoptosis is another mechanism by which vitamin D is suggested to play a role in EBV and KSHV infections ( Figure 5). 117,127,[136][137][138] It has been reported that EBNA-3 is capable of blocking the expression of VDR-dependent genes involved in growth inhibition and apoptosis. 117 Similarly, vitamin D treatment of endothelial cells and cells transformed by the vGPCR of KSHV was shown to increase the proapoptotic protein Bim through a caspase-3-dependent mechanism.…”
Section: Induction Of Autophagy and Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…106,135 Apoptosis is another mechanism by which vitamin D is suggested to play a role in EBV and KSHV infections ( Figure 5). 117,127,[136][137][138] It has been reported that EBNA-3 is capable of blocking the expression of VDR-dependent genes involved in growth inhibition and apoptosis. 117 Similarly, vitamin D treatment of endothelial cells and cells transformed by the vGPCR of KSHV was shown to increase the proapoptotic protein Bim through a caspase-3-dependent mechanism.…”
Section: Induction Of Autophagy and Apoptosismentioning
confidence: 99%
“…Apoptosis is another mechanism by which vitamin D is suggested to play a role in EBV and KSHV infections (Figure ) . It has been reported that EBNA‐3 is capable of blocking the expression of VDR‐dependent genes involved in growth inhibition and apoptosis .…”
Section: Introductionmentioning
confidence: 99%
“…PLS analysis showed clustering of the two study groups (Figure 2), which could not be observed previously when considering all 94 patients (as mentioned in 3.2). For further evaluation, we filtered the data with a log2 fold change of minimum |0.2| and used the resulting 41 genes ( Figure S4 and S5, supplementary information) for analysis of pathways and biological processes (Table 4) both pathways has been implied [40][41][42][43], but its role is not fully understood.…”
Section: Effect Of Serum 25(oh)d Level For Detection Of Vitamin D Depmentioning
confidence: 99%
“…Chronic liver inflammation and the subsequent progression to liver cirrhosis and hepatocellular carcinoma (HCC) are typical clinical symptoms of chronic HCV infection. A significant inverse relationship between the severity of inflammatory fibrosis and cirrhosis and serum 25(OH)D 3 levels was observed in HCV patients [32,33,37,40,[62][63][64]. This implies VD deficiency as an independent predictor and risk factor for inflammatory liver complications in HCV patients [38,39,[65][66][67].…”
Section: Effect Of Vd On Hcv Pathogenesismentioning
confidence: 91%